Optimization of the Construction Subcontractor Selection Process for Residential Building Projects by Applying Blockchain Technology Through a Smart Contract - Janampa, Josue (2024)
Nowadays, the construction industry has become the main and great engine of the global economic recovery after the effects of covid-19, generating around 10.7 trillion dollars worldwide, and it is residential construction, specifically, the one in charge of driving growth in the short term, thanks to the constant demand for residential spaces. In this sense, various challenges such as new technologies, the complexity of projects, and a growing competitive environment, force the main contractor to subcontract between 80 and 90% of the activities, thus evidencing that subcontracting is an applied and necessary process in every construction project, and making subcontractors the backbone of the procurement strategy. However, one of the main risks of subcontracting is the inadequate selection of the construction subcontractor, which is often based solely on the criteria of selecting the known subcontractor and the lowest price, which often leads to risks regarding the time, cost and quality of the project. For this reason, the present research aims to improve the selection of the construction subcontractor carried out by the main contractor, through the development of a new subcontractor selection process, adapted to the current selection process, in which a Smart Contract is incorporated to greatly contribute to trust in the selection process, thanks to the contribution of Blockchain technology, in this process, through security against data manipulation, transparency of the selection process executed, traceability of information in real time pertaining to the process followed, and automation in the selection of the subcontractor under pre-established criteria.